Influence of Textile Structure and Silica Based Finishing on Thermal Insulation Properties of Cotton Fabrics. (8th March 2016) - Rosace, G.; Guido, E.; Colleoni, C.; Barigozzi, G.
Abstract : The aim of this work is to investigate the influence of weave structures and silica coatings obtained via sol-gel process on the thermal insulation properties of cotton samples. For this reason three main weave structures (plain, satin, and piqué) of cotton fabric were selected with different yarn count, threads per cm, and mass per square meter values. Thereafter, only for the plain weave, the samples were padded using silica sol formed by hydrolysis and subsequent condensation of 3-glycidoxypropyltrimethoxysilane under acidic conditions. The silanized plain weave samples were characterized by TGA and FT-IR techniques. The thermal properties were measured with a home-made apparatus in order to calculate thermal conductivity, resistance, and absorption of all the treated fabric samples. The relationship between the thermal insulation properties of the plain weave fabrics and the concentration of sol solutions has been investigated. Fabrics weave and density were found to strongly influence the thermal properties: piqué always shows the lowest values and satin shows the highest values while plain weave lies in between. The thermal properties of treated high-density cotton plain weave fabric were proved to be strongly influenced by finishing agent concentration.